The Urgency of Regulatory Synchronization For "Merah Putih" Village Cooperatives: A Critical Analysis Based On The Theory of The Unity of The Normative Order - Asyif Mahfudz; Septi Nur Wijayanti (International Journal of Educational Research & Social Sciences, 2026)
The government, through the policy of the President of the Republic of Indonesia, instructed the establishment of the Merah Putih Village Cooperative with the aim of empowering the people's economy, empowering MSMEs, and strengthening food sovereignty. This study aims to determine whether there is normative disharmony in the policy of establishing the Merah Putih Village Cooperative. The study uses a juridical-normative method using secondary data, including laws and regulations that underlie the policy, Presidential Instructions, and Government Regulations. The theory of the unity of normative order is used to conduct a conceptual analysis of whether the Merah Putih Village Cooperative policy has the potential for normative disharmony. The results of this study indicate that the policy of establishing the Merah Putih Village Cooperative has normative disharmony, namely the lack of synchronization between policy norms and regulations of the Merah Putih Village Cooperative, namely the existence of overlapping norms that have implications for legal uncertainty in policy implementation. The importance of aligning regulations that underlie the implementation of the Merah Putih Village Cooperative so that they are in line with pre-existing normative order, so that the main objective of establishing the Merah Putih Village Cooperative can be realized by paying attention to the normative basis so as to create legal certainty and effectiveness in its implementation.